Characterization of Micronutrients and Heavy Metal Content in Organic Fertilizer Made From Fly Ash and Organic Waste - Utami, Sari Widya; Tarigan, Roy Aries Permana; Widianingsih, Betti (JOURNAL OF TROPICAL SOILS, 2019)
The production of electrical energy from burning of coal producedÂ  large amounts of fly ash waste. Fly ash had the potential to be used as soil ameliorant material because it has a very fine size. The purpose of the research was to to develop a new alternative organic fertilizer and to find out the contents of micronutrients and heavy metal on organic fertilizer with fly ash matterials. The research was conducted by composting some organic matterials that consisted of fly ash, poultry manure, peanute litter, dusk of ripsaw and "Ares" of banana stalk in some comparisons. The selection of the the best organic fertilizer based on the ranking method. The result of this research showed that the selected organic fertilizer was fertilizer that given 10% of fly ash. TheÂ  micronutrientss content of the organic fertilizer was low for Cu, Mn and Zn element but the Fe element was high. The heavy metals content of the fertilizer was low for As, Cd, Hg and Pb.